1998
DOI: 10.1002/(sici)1096-9861(19980316)392:3<390::aid-cne8>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical and ultrastructural study of the rat perireticular thalamic nucleus during postnatal development

Abstract: The perireticular thalamic nucleus (PRT) consists of scattered neurons that are located in the internal capsule adjacent to the gamma aminobutyric acid (GABA)-immunoreactive (ir) reticular thalamic nucleus (RT) and whose number decreases during development. The common feature of PRT neurons in different species is the immunoreactivity for the calcium binding protein parvalbumin (PV), which is also expressed by RT cells. In this study, we analyzed, at the light and electron microscopic level, the distribution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Presence of calcium-binding proteins such as calbindin, parvalbumin and calretinin, have been described in the RTN by Frassoni et al (1991), Spreafico et al (1991), Clemence and Mitrofanis (1992), Resibois and Rogers (1992), Winsky et al (1992), Lizier et al (1997), Amadeo et al (1998), FitzGibbon et al (2000 and Kakei et al (2001). Calcium binding proteins may exert significant action on membrane potential, synaptic transmission and even on the firing pattern of the related neurons (Baimbridge et al, 1992;Caillard et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Presence of calcium-binding proteins such as calbindin, parvalbumin and calretinin, have been described in the RTN by Frassoni et al (1991), Spreafico et al (1991), Clemence and Mitrofanis (1992), Resibois and Rogers (1992), Winsky et al (1992), Lizier et al (1997), Amadeo et al (1998), FitzGibbon et al (2000 and Kakei et al (2001). Calcium binding proteins may exert significant action on membrane potential, synaptic transmission and even on the firing pattern of the related neurons (Baimbridge et al, 1992;Caillard et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…has many more neurones) than in the adult. With subsequent maturity, the perireticular nucleus becomes reduced in size -by about P (postnatal day) 10 in rats and ferrets -largely by a process of cell death, and only a few neurones remain in the adult (see Mitrofanis 1992a;Adams and Baker 1995;Earle and Mitrofanis 1996; Ramcharan and Guillery 1997;Amadeo et al 1998).…”
Section: Indroductionmentioning
confidence: 99%
“…has many more neurones) than in the adult. With subsequent maturity, the perireticular nucleus becomes reduced in size -by about P (postnatal day) 10 in rats and ferrets -largely by a process of cell death, and only a few neurones remain in the adult (see Mitrofanis 1992a;Adams and Baker 1995;Earle and Mitrofanis 1996; Ramcharan and Guillery 1997;Amadeo et al 1998).During the early stages of development, several studies have shown that although perireticular neurones are labelled from the dorsal thalamus during prenatal development in rats and ferrets, there are many more perireticular neurones labelled during neonatal development (Mitrofanis and Baker 1993;Mitrofanis 1994b). Thus the perireticular projection is heaviest after birth, well after the early connections of the developing forebrain are complete (reviewed Molnàr and Blakemore 1995).…”
mentioning
confidence: 99%
“…These neurons are all generated relatively early in development, and show heavy neuronal loss during later development. The neurons of the perireticular nucleus at early embryonal stages express the same antigens (parvalbumin, pro‐α‐thyrotropin releasing hormone calbindin and GABA+) as the neurons in the reticular nucleus (Mitrofanis, 1992a; Letinic & Kostovic, 1996; Amadeo et al. 1998; Contreras‐Rodriguez et al.…”
Section: Discussionmentioning
confidence: 99%